2013
DOI: 10.1007/s00253-013-5027-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty alcohol production in engineered E. coli expressing Marinobacter fatty acyl-CoA reductases

Abstract: Although successful production of fatty alcohols in metabolically engineered Escherichia coli with heterologous expression of fatty acyl-CoA reductase has been reported, low biosynthetic efficiency is still a hurdle to be overcome. In this study, we examined the characteristics of two fatty acyl-CoA reductases encoded by Maqu_2220 and Maqu_2507 genes from Marinobacter aquaeolei VT8 on fatty alcohol production in E. coli. Fatty alcohols with diversified carbon chain length were obtained by co-expressing Maqu_22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…Our work complements research in production of fatty acid-derived products in other microbial hosts in several ways (Liu et al, 2013;Teixeira et al, 2017). The findings about the ER subcellular localization of MmFar1p (mouse fatty acid reductase) is relevant to engineering pathway compartmentalization as a way to optimize bioproduction or tailor product distribution (Avalos et al, 2013;Sheng et al, 2016;.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our work complements research in production of fatty acid-derived products in other microbial hosts in several ways (Liu et al, 2013;Teixeira et al, 2017). The findings about the ER subcellular localization of MmFar1p (mouse fatty acid reductase) is relevant to engineering pathway compartmentalization as a way to optimize bioproduction or tailor product distribution (Avalos et al, 2013;Sheng et al, 2016;.…”
Section: Discussionmentioning
confidence: 74%
“…Besides our earlier report expressing a Mus musculus FAR in S. cerevisiae (Runguphan and Keasling, 2013), other labs have reported on heterologously expressing a FAR from Tyto alba (Feng et al, 2015) and two from Marinobacter hydrocarbonasticus (Liu et al, 2013;Wahlen et al, 2009;Willis et al, 2011). To determine the variant most effective for fatty alcohol production in S. cerevisiae, we chromosomally integrated the four FAR coding sequences (MmFAR1, TaFAR1, MaFAR2, and MaFAR7, codon-optimized sequences in Suppl.…”
Section: Pull: Comparing Fatty Acyl-coa Reductase Variantsmentioning
confidence: 99%
“…As mentioned previously, additional activities toward fatty acyl-CoA and fatty acyl-ACP have been reported for the fatty aldehyde reductase from M. aquaeolei VT8 since the initial characterization of this enzyme (4,5). Additionally, others have recently demonstrated that the fatty aldehyde reductase (Maqu_2220, or NCBI accession number YP_959486) resulted in improved fatty alcohol yields when heterologously expressed in E. coli versus several other fatty acyl-CoA reductases (21).…”
Section: Resultsmentioning
confidence: 99%
“…While many thioesterases have been ex-plored for long-chain fatty acid production (14)(15)(16)(17), few studies have focused on those that prefer short-chain acyl-CoAs. Several broad-specificity acyl-CoA thioesterases, including E. coli TesB and Saccharomyces cerevisiae Pte1p, can be used for SCFA production but lack the specificity necessary for optimizing biosynthetic pathways (11,18).…”
mentioning
confidence: 99%